2020
DOI: 10.21203/rs.3.rs-135522/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Investigation of AIDS-related Knowledge-Attitude-Practice and Analysis of Influencing Factors Among Students in China

Abstract: Background: With the increasing number of HIV infected students in China, it is necessary to investigate AIDS-related knowledge-attitude-practice among students, which is helpful to formulate effective AIDS health education measures for students.Methods: A cross-sectional study was conducted with students aged 15-24 years. University college students (n=1,744) were surveyed with a sampling in western China. The data were collected from May to November 2019 through both face-to-face and online survey. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Adherence to nutritional interventions is an important factor influencing the effectiveness of the study. Studies have shown that high adherence with family interventions for ASD facilitates treatment delivery, helps relieve patients' symptoms and improves their intelligence [50]. Patient adherence control does have a direct impact on the effectiveness of studies of omega-3 supplementation in patients with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to nutritional interventions is an important factor influencing the effectiveness of the study. Studies have shown that high adherence with family interventions for ASD facilitates treatment delivery, helps relieve patients' symptoms and improves their intelligence [50]. Patient adherence control does have a direct impact on the effectiveness of studies of omega-3 supplementation in patients with ASD.…”
Section: Discussionmentioning
confidence: 99%